Megalith quarries for Stonehenge's bluestones. (18th February 2019) - Pearson, Mike Parker; Pollard, Josh; Richards, Colin; Welham, Kate; Casswell, Chris; French, Charles; Schlee, Duncan; Shaw, Dave; Simmons, Ellen; Stanford, Adam; Bevins, Richard; Ixer, Rob
Abstract: Abstract : Geologists and archaeologists have long known that the bluestones of Stonehenge came from the Preseli Hills of west Wales, 230km away, but only recently have some of their exact geological sources been identified. Two of these quarries—Carn Goedog and Craig Rhos-y-felin—have now been excavated to reveal evidence of megalith quarrying around 3000 BC—the same period as the first stage of the construction of Stonehenge. The authors present evidence for the extraction of the stone pillars and consider how they were transported, including the possibility that they were erected in a temporary monument close to the quarries, before completing their journey to Stonehenge.